The Influence of Product Innovation and Digital Marketing on Sales Volume with Purchase Intention as an Intervening Variable: A Case Study of Generation Z in Semarang City - M Shifa Zulfikar; Rr. Hawik Ervina Indiworo; Ratih Hesty Utami Puspitasari (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims aims to determine the influence of product innovation and digital marketing on sales volume with purchase intention as an intervening variable on Frisian Flag products. The population in this study consists of Generation Z in Semarang City, and the sample was determined using the purposive sampling method with criteria including respondents who belong to Generation Z (born between 1997–2012), are residents of Semarang, and have purchased Frisian Flag products. The analytical method used in this study is Partial Least Squares (PLS) with the SmartPLS version 3.2.9 software. The results of the analysis indicate that product innovation has a positive and significant effect on both purchase intention and sales volume. Digital marketing does not have a direct effect on sales volume but has a positive and significant effect on purchase intention. Furthermore, purchase intention acts as a mediating variable that strengthens the relationship between product innovation, digital marketing, and sales volume.